Benign surgical emphysema of the hand and upper limb: gas is not always gangrene—a report of two cases. Issue 11 (22nd October 2007) - Fox, A; Sheick, H; Ekwobi, C; Ho-Asjoe, M
Abstract : Subcutaneous emphysema of the hand can result from benign causes. Differentiating this from emphysema caused by gas-forming organisms is essential in the acute stages of presentation as the management differs considerably. We present two cases of benign surgical emphysema and highlight the importance of distinguishing between this and gas gangrene. A considered history and the absence of systemic features associated with benign causes of subcutaneous air will prevent unnecessary surgical exploration.